Dengue versus COVID-19: comparing the incidence of cardiovascular, neuropsychiatric and autoimmune complications - Wee, Liang En (2024)
Background: While persistence of chronic symptoms following dengue infection has been documented in small prospective cohorts, population-based studies are limited. The post-acute risk of new-incident multi-systemic complications following dengue infection was contrasted against that following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in a multi-ethnic adult Asian population. Methods: National testing and healthcare claims that databases in Singapore were utilized to build a retrospective population-based adult cohort with laboratory-confirmed infection during overlapping waves of SARS-CoV-2 and dengue transmission (1 July 2021 to 31 October 2022). Risks of new-incident cardiovascular/neuropsychiatric/autoimmune complications 31-300 days of post-dengue infection, contrasted with SARS-CoV-2 infection, were estimated using Cox regression with overlap weights. Risks were reported in terms of adjusted hazard ratio (aHR) and excess burden per 1000 persons. Results: 11 707 dengue-infected individuals and 1 248 326 contemporaneous coronavirus disease 2019 (COVID-19) cases were included; the majority had mild initial infection not requiring hospitalization. Amongst dengue-infected individuals, there was 21% [aHR = 1.21 (1.06-1.38)] increased risk of any sequelae, with 55% [aHR = 1.55 (1.27-1.89)] increased risk of cardiovascular sequelae. Specifically, increased risk of dysrhythmias [aHR = 1.79(1.35-2.37)], ischemic heart disease [aHR = 1.45(1.12-1.89)], other cardiac disorders [aHR = 2.21(1.54-3.16)] and thrombotic disorders [aHR = 2.55(1.50-4.35)] was noted. Elevated risk of individual neuropsychiatric sequelae, including cerebrovascular disorders [aHR = 1.49(1.09-2.13)], cognition/memory disorders [aHR = 2.13(1.55-2.93)], extrapyramidal/movement disorders [aHR = 1.98(1.33-2.94)] and anxiety disorders [aHR = 1.61(1.01-2.56)], was observed in dengue-infected individuals compared to COVID-19 cases. Elevated risks of post-acute sequelae in dengue survivors were observed when contrasted against COVID-19 survivors infected during Delta/Omicron predominance, as well as across vaccination strata. Conclusion: Increased risk of post-acute cardiovascular/neuropsychiatric complications was observed in dengue survivors, when contrasted against COVID-19 survivors infected during Delta/Omicron predominance.